Fetal Programming of the Neuroendocrine-Immune System and Metabolic Disease. (16th August 2012) - Fisher, R. E.; Steele, M.; Karrow, N. A.
Abstract : Adverse uterine environments experienced during fetal development can alter the projected growth pattern of various organs and systems of the body, leaving the offspring at an increased risk of metabolic disease. The thrifty phenotype hypothesis has been demonstrated as an alteration to the growth trajectory to improve the survival and reproductive fitness of the individual. However, when the intrauterine environment does not match the extrauterine environment problems can arise. With the increase in metabolic diseases in both Westernized and developing countries, it is becoming apparent that there is an environmental disconnect with the extrauterine environment. Therefore, the focus of this paper will be to explore the effects of maternal malnutrition on the offspring's susceptibility to metabolic disorders such as obesity, cardiovascular disease, and diabetes with emphasis on programming of the neuroendocrine-immune system.